Transition‐Metal‐Free Cross‐Coupling of Arylsilanes with DAST Reagent: Synthesis of Aromatic Sulfinamides. Issue 25 (2nd July 2020) - Liu, Zhenwei; Liu, Xinya; Luan, Nannan; Geng, Yang; Liang, Apeng; Li, Jingya; Zou, Dapeng; Wu, Yusheng; Wu, Yangjie
Abstract: A transition‐metal‐free cross‐coupling of arylsilanes with DAST (diethylaminosulfur trifluoride) reagent has been developed. A number of aromatic sulfinamides were obtained in reasonable yields (15%‐87%). Notable advantages of this method include easy operation, mild reaction conditions and wide substrate scope. Abstract : A transition‐metal‐free cross‐coupling of arylsilanes with DAST (Diethylaminosulfur trifluoride) reagent has been developed. Using 2.5 equiv. of NaHCO3 as base in DCM (4.0 mL) at room temperature, a variety of aromatic sulfinamides were synthesized from arylsilanes. A plausible mechanism was proposed which underwent a nucleophilic sulfuration process.